2017
DOI: 10.1139/cjss-2016-0153
|View full text |Cite
|
Sign up to set email alerts
|

Long-term agricultural land use affects chemical and physical properties of soils from Southwest Saskatchewan

Abstract: Understanding nutrient cycling under different land uses can improve agricultural management practices. In southwestern Saskatchewan, long-term land use as annual cropland, native grassland pasture, tame (planted) crested wheatgrass grasslands, or roadsides altered soil physical and chemical properties based on the intensity and frequency of disturbance, with cropland > roadsides > tame grassland > native grassland. The majority of significant differences were detected at the soil surface (0-7.5 cm); few signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…At each location, six soil cores (1.9 cm diameter) were collected inside four 1 m 2 quadrats that were situated along a 10 m transect for a total of 24 total soil cores per location. This differs from Cade-Menun et al (2017a) with respect to date, sampling depth and number of study sites. Soil samples were stored in a cooler with ice packs while in the field.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…At each location, six soil cores (1.9 cm diameter) were collected inside four 1 m 2 quadrats that were situated along a 10 m transect for a total of 24 total soil cores per location. This differs from Cade-Menun et al (2017a) with respect to date, sampling depth and number of study sites. Soil samples were stored in a cooler with ice packs while in the field.…”
Section: Methodsmentioning
confidence: 97%
“…The four experimental sites [Auvergne Wise Creek (AWC), Val Marie (VM), Masefield (MF1, MF2)], located in southwestern Saskatchewan, have the same soil type (well-drained Orthic Brown Chernozems; Saskatchewan Environment, and Resource Management [SERM], 1997 ) and a known history of more than 50 years in each studied land use type ( Cade-Menun et al, 2017a ). The native grasslands were a mixed grass prairie community, and tame grasslands were crested wheatgrass [ Agropyron cristatum (L.) Gaetern.]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in a study in the UK that arable soils were dominated by orthophosphate, while extensively-grazed grassland soils were dominated by OP compounds (Stutter et al 2015). Further, it was reported that cropland soils in Canada contained decreased OC and OP and increased easily available IP contents compared to grassland soils (Cade-Menun et al 2017). However, the loss of OP relative to OC caused by land-use conversion and the role of minerals for the stabilization of OP is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%